Poincaré type inequality for Dirichlet spaces and application to the uniqueness set - Kellay, Karim (Mathematica Scandinavica, 2011)
We give an extension of Poincaré's type capacitary inequality for Dirichlet spaces and provide an application to study the uniqueness sets on the unit circle for these spaces.